(untitled) (Colloquium Agrariae. ISSN: 1809-8215, 2019)
The Cerrado biome has great biodiversity and also includes part of the agricultural production of the country being used for the cultivation of large crops. The nematode of the Meloidogyne incognita galls can cause significant losses in the cotton crop, as well as the fungus Sclerotinia sclerotiorum that causes damage to several crops of economic importance. Among the microorganisms with potential for phytopathogen control, actinomycetes are known for the ability to produce compounds with antimicrobial action. The objective of this work was to isolate and evaluate the antagonistic potential of actinomycetes of native soils of the Cerrado Baiano area against M. incognita and S. sclerotiorum. It was obtained 18 isolates of actinomycetes and among the tested isolates, AC. O, presented the highest percentage of immobility with 99.16% and AC. R, showed the highest percentage of mortality with 72.16% of the J2 of M. incognita. Effective control of M. incognita in cotton was not observed in vivo. However, with the rotation system with soybean, the AC isolate. G, showed a significant reduction in the number of galls and eggs in the cotton root system. With respect to the antagonism of actinobacteria against S. sclerotiorum, by the pairing of cultures, the isolate AC. M, inhibited 81.99% of the mycelial growth of this phytopathogen. The results of the present work show the potential of control of phytopathogens tested by actinomycetes, since a great part of cotton production is found in Cerrado areas and these microorganisms were isolated from this biome.